Association Between Heat Stress Exposure, Physical Activity, and Nutritional Status with Occupational Fatigue: Pilot Study - Kusmawan, David; Perdana, Silvia M.; S., Putri Irwanti; Gustina, Ira; Bowolaksono, Anom; Firmansyah, Ardi (Unnes Journal of Public Health, 2025)
Global economic losses from workplace heat and reduced labor productivity are projected to reach nearly US$2 trillion by 2030. The rubber processing industry is particularly vulnerable to heat exposure. This study aimed to describe worker sociodemographic characteristics and assess the relationship between perceived heat stress, nutritional status, physical activity, and occupational fatigue among employees at PT. X in Jambi Province. A cross-sectional design with purposive sampling involved 74 workers across three production areas. Fatigue was measured using the Swedish Occupational Fatigue Inventory (SOFI), while perceived heat stress was assessed with the Heat Stress Perception Index (HSSI). Data were analyzed with univariate and multivariate methods, including multiple linear regression. Participants had a mean age of 34.03 years, BMI of 25.88, and oxygen saturation of 98.01%. The mean heat stress perception score was 50.31, and occupational fatigue averaged 40.55. Lack of energy was the most reported fatigue dimension (mean = 49.23), whereas lack of motivation was the least (mean = 29.92). Regression analysis identified gender (p = 0.003), physical activity (p = 0.031), and perceived heat stress (p = 0.035) as significant predictors. These findings highlight the need for targeted occupational health interventions to mitigate fatigue in the rubber processing industry